2004
DOI: 10.1152/ajpcell.00275.2003
|View full text |Cite
|
Sign up to set email alerts
|

An LQT mutant minK alters KvLQT1 trafficking

Abstract: Cardiac IKs, the slowly activated delayed-rectifier K+ current, is produced by the protein complex composed of α- and β-subunits: KvLQT1 and minK. Mutations of genes encoding KvLQT1 and minK are responsible for the hereditary long QT syndrome (loci LQT1 and LQT5, respectively). MinK-L51H fails to traffic to the cell surface, thereby failing to produce effective IKs. We examined the effects that minK-L51H and an endoplasmic reticulum (ER)-targeted minK (minK-ER) exerted over the electrophysiology and biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
72
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 45 publications
11
72
1
Order By: Relevance
“…Indeed, previous studies clearly showed that KCNE1 increased KCNQ1 current and modified the electrophysiological properties of the KCNQ1 channel (half-activation potential and kinetics of inactivation) (19, 28 -30). In addition, although more contradictory, previous studies also reported increased trafficking of KCNQ1 when co-expressed with KCNE1 (31). Finally, the chaperone role that we propose for KCNE1 is consistent with previous publications showing that ␤-subunits stabilize and enhance the trafficking of other channels (32,33).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, previous studies clearly showed that KCNE1 increased KCNQ1 current and modified the electrophysiological properties of the KCNQ1 channel (half-activation potential and kinetics of inactivation) (19, 28 -30). In addition, although more contradictory, previous studies also reported increased trafficking of KCNQ1 when co-expressed with KCNE1 (31). Finally, the chaperone role that we propose for KCNE1 is consistent with previous publications showing that ␤-subunits stabilize and enhance the trafficking of other channels (32,33).…”
Section: Discussionsupporting
confidence: 90%
“…For KCNQ1 channels, coassembly could occur later in biosynthesis because the subunit specificity domain for tetramerization resides in the C terminus (27). In either case, to exploit the dimer-of-dimers pathway, coassembly would have to occur in the endoplasmic reticulum, which is consistent with previous assembly studies with wild-type (28) and mutant KCNE1 peptides (29).…”
Section: Discussionsupporting
confidence: 84%
“…A chaperone effect may contribute, as has been suggested for other KCNE interactions (19). However, we did not consistently observe increased recovery of HCN2 protein in the membrane fraction of ventricular cultures co-expressing HCN2 and HA-MiRP1, compared with those expressing HCN2 alone.…”
Section: Discussioncontrasting
confidence: 42%